’KARSTEN’ DALAM PERENCANAAN KOTA DAN PEMUKIMAN DI KOTA MALANG - Ana Christalina Siuriwati Suryorini (Universitas Muhammadiyah Jakarta, 2010)
ABSTRACT. The industrial revolution in Europe make an impact on the development of big cities in Indonesia especially producing region for industrial raw materials in Europe. Political ethics reciprocation by the Netherlands to the Indonesian nation manifested in urban planning, among others, improvement of quality and environmental management due to the increase of the Dutch people who go to big cities and towns in the Netherlands Indies plantation. Malang City as the region surrounded by plantations developed quite rapidly in 1917 as a residential area planned by Ir. Herman Thomas Karsten Dutch city planners. This study uses data exploration methods using observational study of literature and documentation. In the first stage described the concept of town owned by Ir. Thomas Karsten. In the second phase, analysis of case planning by the city of Malang, Ir. Herman Thomas Karsten. This research has produced: the concept of